Design optimization of a diesel connecting rod - Muhammad, Aisha; Ali, Mohammed Abdo Hashem; Shanono, Ibrahim Haruna (Elsevier Ltd, 2020)
Connection rods are mechanical components used for generating motion from a crankshaft’s piston alternating motion. The credibility and performance of vehicles depends on the design of the connecting rod. There have been numerous reported cases of connecting rod failure based on the structural design, loading type and the type of materials used in its production. To insure safety and satisfies customers demand in automotive industries a robust and optimized connecting rod is required. The aim of this paper is to carryout topology and structural optimization of a connection rod suitable for diesel engine applications. Weight optimization of the connection rod is carried out with target weight reduction of 20%, 30%, 40%, 50%, and 60% under a static loading of 100N, which determines the mass that needs to be remove to minimize both weight and cost without compromising it reliability and durability. Furthermore, the deformation, stress, strain and factor of safety under the same loading condition was compared before and after a 60% target weight reduction. Under a loading condition of 500N, analysis for the structural optimization is done to determine an optimized structure with new deformation and Von-misses stress, equivalent elastic strain, and safety factor values. Comparison of the static structural deformation, Von-misses stress, elastic strain and safety factor before and after the optimization is carried out. Based on the results obtained, it can be concluded that ANSYS software can be employed by production companies to minimize material wastages and maximize profits at the same time maintaining product quality and reliability.